2018
DOI: 10.1016/j.scitotenv.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen inputs drive nitrogen concentrations in U.S. streams and rivers during summer low flow conditions

Abstract: Ecological and human health impairments related to excess nitrogen (N) in streams and rivers remain widespread in the United States (U.S.) despite recent efforts to reduce N pollution. Many studies have quantified the relationship between N loads to streams in terms of N mass and N inputs to watersheds; however, N concentrations, rather than loads, are more closely related to impacts on human health and aquatic life. Additionally, concentrations, rather than loads, trigger regulatory responses. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 97 publications
4
30
1
Order By: Relevance
“…Other regional and national studies relating terrestrial nutrient balances and water quality have identified hydrology as an important driver, including at the national scale for TP (Metson et al, 2017), along the West Coast of the U.S. for TN (Schaefer et al, 2009; Sobota et al, 2009), and for the Northeastern U.S. over time for both TN and TP (Hale et al, 2015). At the national scale, interannual variability in precipitation drives nutrient export over time, but inputs drive patterns in space (Bellmore et al, 2018; Sinha & Michalak, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Other regional and national studies relating terrestrial nutrient balances and water quality have identified hydrology as an important driver, including at the national scale for TP (Metson et al, 2017), along the West Coast of the U.S. for TN (Schaefer et al, 2009; Sobota et al, 2009), and for the Northeastern U.S. over time for both TN and TP (Hale et al, 2015). At the national scale, interannual variability in precipitation drives nutrient export over time, but inputs drive patterns in space (Bellmore et al, 2018; Sinha & Michalak, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to marine and lake ecosystems, streams and rivers may respond differently to N and P enrichment because of stronger terrestrial linkages (e.g., geology, land use, dependence on terrestrial organic matter; Tank et al 2010), stronger influence of hydrology (Green and Finlay 2010, Leong et al 2014), and associated biogeochemical processes that are unique to the unidirectional flow of water (nutrient spiraling; Newbold et al 1983). Therefore, stream and river biogeochemical processes likely interact in complex ways with point and non‐point nutrient inputs from human activities to affect dissolved and particulate nutrient transport to lakes and coastal zones (Alexander et al 2008, Dodds and Smith 2016, Bellmore et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…While acknowledging these excellent research projects, a national scale assessment with monthly, yearly, and decadal timescales seems justified. Although there are a few national-scale studies, their scope, objective, and approach are different from this project [16][17][18].…”
Section: Introductionmentioning
confidence: 99%